Forensic imaging: a practical guide - Dédouit, Fabrice; Yen, Kathrin; Heinze, Sarah (Springer International Publishing, 2022)
Forensic Imaging – A New Subspeciality of Radiology -- Imaging Methods -- What can the Clinical Radiologist Learn from Forensic Imaging? – Analogies and Differences Between Forensic and Clinical Imaging -- PART I - Typical “Normal” Postmortem Findings -- Postmortem Changes -- Normal Postmortem Imaging Findings in Fetuses and Children -- Miscellaneous: Artefacts (Mummification, Conservation, Adipocere, Taphonomy and Artefacts) -- PART II - Examples for Typical Traumatic Forensic Cases -- Examples for Typical Traumatic Forensic Cases: Blunt, Gunshot, Sharp Wounds -- Asphyxia -- Child Abuse, A Post-Mortem Forensic Perspective -- Post-Mortem Computed Tomography of Charred Victims in Modern Forensic Medicine -- PART III - Examples for Typical Non Traumatic Forensic Cases -- Natural Death -- Death at Hospital and Medical Liability: Investigation of Medical Interventions with Fatal Outcome by Post-Mortem Computed Tomography.